Study of Non-star Hotel Sanitation in Kupang City - Da Costa, Maharany Lesthyn; Ruliati, Luh Putu; Sir, Amelya B (Timorese Journal of Public Health, 2021)
The main problem in hotel sanitation generally focuses on the health of the building and environment, for example, the absence of equipment to prevent the entry of insects, an unclean environment,health of sanitation facilities, namely the absence of waste disposal and hotel waste disposal, the provision of clean water, the health of the hotel rooms,lack of lighting, there is no employee rest room. All of these factors can increase the risk of a number of diseases and health problems in non star hotel. The design of this study used an observational design with a descriptive method. The sample of this research is 15 non-star hotels. The sample criteria include hotels that are still actively operating. Sampling using total sampling. The instrument in the form of an observation sheet/inspection form refers to the Regulation of the Minister of Health Number 80 of 1990 concerning the requirements for hospitality sanitation and the Decree of the Director General of PPM and PLP No. 95 of 1991 concerning the Assessment of Hotel Health Checks. The result showed that the four components studied were environmental health & buildings that did not meet the requirements there are the building was still possible as a breeding ground for rats, the floor of the building was slippery, the rooms and hotel rooms did not have an employee rest room, and the warehouse was not well organized, facilities sanitation has met the requirements, and employee health has not met the requirements, namely not having a health certificate from a doctor that is still valid. Recommendations to the hotel to improve hotel sanitation for every nonstar hotel in Kupang City.